Isolation of nanocrystalline cellulose from Leucaena leucocephala (Lam.) de Wit pods and its application as a fat replacer in production of low-fat mayonnaise - Aridi, Aida Safina (2022)
This study investigated the properties of nanocrystalline cellulose (NCC) isolated from L. leucocephala mature pods. Four different bleaching agents were used during the bleaching process, followed by sulphuric acid hydrolysis. Physical and chemical properties, crystallinity index, water binding capacity, and thermal behaviour of obtained NCC were determined by using transmission electron microscopy (TEM), Fourier transforms infrared (FTIR), X-ray diffraction (XRD) and thermogravimetric analysis (TGA), respectively. The results showed individual fibres of rod-shaped particles with a nano-sized average diameter (17 to 49 nm) and length (133 to 239 nm) in all NCC produced. The FTIR spectra indicated that the peaks attributed to lignin and hemicellulose were absent after chemical and bleaching treatment and seems that both components were completely removed from the samples after acid hydrolysis. The XRD analysis showed that crystallinity increased after acid hydrolysis, indicating the isolated NCC's crystalline nature for all samples. NCC treated with 7% sodium hypochlorite shows the highest crystallinity that is 71.1% even though cellulose degradation occurs in the bleaching stage. TGA analysis displayed that degradation of NCC occurred at 143 C֯ , and the Tmax was at 188 C֯ with 25.9% residue at 600 C. A three-region viscosity profile seen in liquid crystalline systems was observed in sonicated samples. Besides that, from Power law, it can be concluded that NCC suspension behaves as a shear-thinning material. Further work was carried out to produce low-fat mayonnaise with isolated NCC as a fat replacer. The mayonnaise with 30% of oil reduction was prepared and incorporated with NCC, MCC, and MCC+NCC (1:1). Both control and mayonnaise with fat replacer appeared stable even after one month of storage. The oil reduction in mayonnaise does affect the colour as all fat-reduced mayonnaise had greater brightness (L*) than the control sample. Besides that, when fat was replaced by NCC, a* increased significantly, whereas b* decreased after storage. All samples showed stable emulsion even after 1 month of storage. The particle size of oil emulsion for all mayonnaise was within the range of theory, between 200 to 500 nm. The rheological properties of mayonnaise produced showed the shear thinning behaviour. From all obtained results, mayonnaise with NCC as a fat replacer shows the best stability.